The Role of Open And Distance Learning in Refreshing Skills of The Alumni. The Casestudy Of The Masvingo Regional Campus, Zimbabwe Open University - Dumbu, Emmanuel; Musingafi, Maxwell (Asian Journal of Empirical Research, 2013)
The study sought to interrogate the short courses that the Zimbabwe Open University Alumni suggest the university to introduce to fill in the gap of the professional skills created by distance learning which are thought to be provided through face to face learning and teaching methods in the from of short courses. A convenient sampling sample of 50 Zimbabwe Open University alumni members who had converged for the alumni Masvingo workshop in November 2010 participated in the study. The study used a qualitative research design whereby questionnaire with open-ended items were use to solicit the professional skills that the alumni feel should fill the gap between academic and professional skills using the short courses. Data was qualitatively analyzed thematically. Findings indicated that the Zimbabwe Open University should unleash a number of professional gap filling courses using the short courses mode to the former students. It also emerged from this study that the alumni expect short courses in supervisory skills, communication skills, time management, office management, dial a smile for the customer and mentorship. The study recommends that the university should introduce short courses in training of trainers’ program, supervisory, communication, time management, dial a smile for the customer and mentorship.